Draft Annual Plan 1982-83 Volume VI General Areas Government of Assam - Planning Commission (Planning Commission, 1982)
Construction of the buildings of district hospitals at Dhubri and North Lakhinpur in new sites, new Sub-Divisional Hospital at Lhemaji and Marigaon and minor extention works in Nowgong, Tezpur, Hailakandi and Mangaldoi Civil Hospitals are in progress. Action has been taken to augment the staff by opening and posting specialist in various disciplines in Sub-Divisional and District Hospitals.
Government of Assam, Planning and Development Department